Effectiveness of Project-Based Learning Model to Enhance Students' Creativity in Secondary Schools - Irawan, Dedi; Muammar Rinaldi; Sri Rezeki (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to analyze the effectiveness of the Project-Based Learning (PjBL) model in improving student creativity in secondary schools. Student creativity includes four main aspects, namely fluency, flexibility, originality, and elaboration. The study was conducted using a quantitative approach with a quasi-experimental design, involving two groups of students: an experimental group using the PjBL method and a control group using conventional learning methods. Data were collected through observation, creativity tests, and student learning motivation questionnaires. The results showed that the implementation of PjBL had a significant effect on increasing student creativity. Students in the experimental group showed higher creativity scores than the control group, with the most striking increase in the aspects of originality and elaboration. In addition, the PjBL model also increased student learning motivation as well as collaboration, critical thinking, and problem-solving skills. The integration of technology in PjBL, such as the use of digital devices and online resources, had a positive impact on students' learning experiences. However, this study also found several obstacles in the implementation of PjBL, such as the need for teacher training, time management, and infrastructure support. Therefore, a comprehensive strategy is needed to optimize the implementation of PjBL in secondary schools. Overall, the project-based learning model has proven to be effective in enhancing student creativity and is relevant to the demands of 21st century education.